2015
DOI: 10.1007/s00384-015-2265-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of preoperative CT scan to stratify colon cancer for neoadjuvant therapy

Abstract: Computer tomography represents an effective tool for identifying patients with colon cancer suitable for neoadjuvant therapy according to the guidelines for rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
(28 reference statements)
2
6
0
Order By: Relevance
“…The potential for using CT to produce a valid cTN stage has been discussed in several other studies. Some previous studies have shown acceptable agreement between cTN and pTN (5, 9), while others have, as in the present study, shown poor levels of agreement (10,11). Although some studies have presented moderately superior results compared to the current study, they have all struggled to identify high-risk tumors (4,6,911).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The potential for using CT to produce a valid cTN stage has been discussed in several other studies. Some previous studies have shown acceptable agreement between cTN and pTN (5, 9), while others have, as in the present study, shown poor levels of agreement (10,11). Although some studies have presented moderately superior results compared to the current study, they have all struggled to identify high-risk tumors (4,6,911).…”
Section: Discussionsupporting
confidence: 46%
“…The modality most often used is computed tomography (CT) (3). Usage of CT in the staging of distant metastases (M) is well established (3) and some studies have indicated that CT is a valid method for determining tumor and nodal stage (4,5). These results, however, have been contradicted by a recent study from Sweden by Sjövall et al.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of KRAS mutation in CRC is always associated with advanced tumor stage and presence of lymph node metastasis with poor response to treatment and outcome [2,20,23,33,41,42]. For most CRC, CT is the routinely used imaging modality for tumor diagnosis, tumor staging, identifying patients who require neo-adjuvant therapy, and assessing treatment response [43][44][45][46]. Recently, some reports have found that new generation CT scanners can offer high spatial resolution images with reliable rectal staging with low dose of radiation, particularly useful in patients who have contraindication to MRI [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Even though the rationale underlying the decision to limit preventive measures to avoid peritoneal recurrence only to patients with pT4 tumors seems correct, in clinical practice identifying pT4 tumors preoperatively with the current diagnostic tools seems an almost impossible task. Multidetector computed tomography (MDCT) is highly accurate in distinguishing pT1-2 from pT3-4 tumors, but differentiating between pT3 and pT4 tumors remains a challenging task [81][82][83][84]. A correct differential diagnosis between pT3 and pT4 tumors is even difficult macroscopically unless tumor filtrates clearly into adjacent organs, and often requires a thorough pathologic assessment [85].…”
Section: Proactive Management Of Peritoneal Metastases From Colorectamentioning
confidence: 99%